Taṭwīr māddah al-Lughah al-‘Arabiyyah bi Tasmīm al-Kitāb al-Muqarrar li al-Talāmidz fī TPQ Plus Baiturrahman Banda Aceh - Siti Rahmah (Universitas Islam Negeri Ar-Raniry Banda Aceh, Aceh, Indonesia., 2020)
Teaching material is a key factor of the learning process and has an important role in the learning process. With teaching material, students not only rely on teacher explanations but also can learn on their own, not only from books, but also from tapes. Arabic is one of the lessons learned by students at TPQ Plus Baitur Rahman, Banda Aceh. In this study the researcher wanted to explain the steps in developing books, how to use the book in teaching and learning process, and the effectiveness of using the book in TPQ Plus Baitur Rahman. Research and Developmentmethod was used is this research. The data was obtained by using tests, questionnaires, and interviews.